Analisis Perbandingan Prediksi Financial Distress Pada Bank Umum Syariah di Indonesia dan Malaysia Periode 2017-2021 Menggunakan Metode Altman Z-Score Modifikasi - Muhamad Alif Nur Faizy; Ade Ali Nurdin; Ine Mayasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to determine the differences in the prediction results of financial distress at Islamic Commercial Banks in Indonesia and Islamic Commercial Banks in Malaysia and to determine the effect of the variable ratios of NPF, CAR and FDR on financial distress. The data analysis method uses the Mann Whitney differential test, the results show that there are differences. besides that the data analysis technique used is panel data regression analysis, simultaneously the ratio of NPF, CAR and FDR affects the value of the Z-Score or financial distress. In Islamic Commercial Banks in Indonesia, partially NPF has no effect on the value of the Z-Score or financial distress. Meanwhile, the CAR and FDR ratios have a positive effect on the Z-Score or financial distress. At Islamic Commercial Banks in Malaysia partially the NPF and CAR ratios have no effect on the Z-Score or financial distress, while the FDR ratio has a negative effect on the Z-Score or financial distress.